KEEFEKTIFAN METODE PERMAINAN SECRET MESSAGE DALAM KETERAMPILAN MENULIS PADA MATA KULIAH SAKUBUN II (Penelitian Eksperimen Terhadap Mahasiswa Tingkat II Tahun Ajaran 2016/2017 Pendidikan Bahasa Jepang FKIP UR) - Putri, Shinta Dwi; Rahayu, Nana; Widiati, Sri Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to find out the difference of studentâ€™s ability in writing Japanese essays (sakubun) after implementing Secret Message Game. The research is conducted using weak experimental type one group pre test post test design. The object of this research is 16 second-level students as the respondents. The sample is taken by using simple random sampling technique. Data collection was performed by giving test and questionnaire. The given test was writing Japanese essays (sakubun) with the topic â€œhobbyâ€. The writer applies two tests, they are pre test and post test. Pre test is given before the students are taught by implementing Secret Message Game, and post test is given after the students are taught with Secret Message Game. This research is processed by paired sample t-test using software of SPSS Version 16 in order to know whether Ha is accepted or not. Based on the data analysis, the value of the post test in writing Japanese essays is lower than 0,05 (0,000 < 0,05). It means that Ha is accepted and H0 is rejected. Besides that, most students agree that this game is effectively helping to write Japanese essays (sakubun) easily. The result of this research is that there is a significant impact of using Secret Message Game in learning of Japanese essays (sakubun) on the second-level students of Japanese Education Department Faculty of Teacherâ€™s Training and Education Riau University.Key Words: Sakubun, Secret Message Game, Writing Skill